Are the Malaysian adolescents’ behavior at-stake? - Abd. Hamid, Siti Rafiah; Ismail, Khamsiah; Saad, Supiah; Ibrahim, Mohd Burhan; Mansor, Norwati (MCSER-CEMAS-Sapienza University of Rome, 2015)
This study explored attributes of at-risk behaviors amongst Malaysian adolescents in secondary school and factors underpinning these behaviors. Clustered random sampling procedure was administered and approximately 738 respondents’ questionnaires were finally considered for the final analyses of the data collected. A survey form which comprised demographic variables, types of at-risk behaviors and factors affecting them was pilot-tested and administered. Descriptive statistics (namely mean scores and standard deviations) was employed to describe the demographic variables related to Malaysian adolescents and types of at-risk behaviors prevalent among Malaysian adolescents. Inferential statistics (Anova and t-tests) were administered for comparing gender, age, and location – urban versus rural, family SES differences as regard to the type of at risk behaviors prevalent. Findings based on the descriptive statistic and inferential statistics indicated that incidences of at-risk behaviors such as substance abuse, alcohol consumptions, suicide ideations and attempts, pre-marital sex, teen pregnancy and abortion, runaways were minimal and not alarming. Findings from this study shed light on the importance of developing intervention strategies which involved all quarters namely; parents, school, society and positive portrayal of adolescents’ image and icons via media in our attempt to improve the life quality of adolescents.